Pengenaan Pajak Pertambahan Nilai Terhadap Jasa Intermediasi Keuangan Perbankan Di Indonesia - Setiadi Alim Lim (BIP's JURNAL BISNIS PERSPEKTIF, 2015)
Most countries that use the Value Added Tax system are generally exclude financial intermediation services of imposition of Value Added Tax. This exception in addition to reduce the country revenue from tax sector in significant numbers, also gives rise to distortions in terms of both legal and economical. But after the financial crisis in 2008, many countries have began to rethink to impose value added tax on financial intermediation services. There are several alternative methods are expected to be implemented to overcome the difficulties the imposition of VAT on financial intermediation services. Indonesia as one of the countries that use the Value Added Tax system also excludes the imposition of VAT on financial intermediation services. In order to increase country revenuefrom the tax sector, the Indonesia should consider eliminating VAT exemption for financial intermediation services.